The Effectiveness of Pagar Alam Green Tea Leaf Extract (Camellia sinensis L.) as an Irrigation Material on Smear Layer Removal - Rhamasuci Putri Jasa; Merryca Belinda; Listia Eka Merdekawati; Danica Anastasia (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: The smear layer is a by-product of root canal instrumentation that may interfere with effective canal disinfection. Irrigation plays a crucial role in removing debris, microorganisms, and smear layer, particularly in the apical third, which is difficult to clean due to anatomical complexity. Pagar Alam green tea leaf extract (Camellia sinensis L.) has been proposed as a natural alternative irrigation material with potential smear layer removal properties. Purpose: To determine the concentration of Pagar Alam green tea leaf extract that effectively removes smear layer. Methods: This quasi-experimental study used 24 mandibular premolar teeth divided into four treatment groups. Root canals were prepared using the crown-down technique with hand ProTaper instruments and irrigated as follows: Group A: 25% Pagar Alam green tea leaf extract; Group B: 50% Pagar Alam green tea leaf extract; Group C: 2.5% NaOCl followed by 17% EDTA; and Group D: distilled water. The samples were sectioned longitudinally and evaluated under a measuring microscope at 1000× magnification using a visual scoring system. Data were analyzed using the Kappa test, Kruskal–Wallis test, and Mann–Whitney test. Results: There was no statistically significant difference in smear layer removal between Group B (50% Pagar Alam green tea leaf extract) and Group C (2.5% NaOCl and 17% EDTA) (p > 0.05). Conclusion: A 50% concentration of Pagar Alam green tea leaf extract is effective in removing the smear layer in the apical third of the root canal.